2011
DOI: 10.1161/circoutcomes.110.958959
|View full text |Cite
|
Sign up to set email alerts
|

Center Variation in Hospital Costs for Patients Undergoing Congenital Heart Surgery

Abstract: Background Congenital heart disease consumes significant health care resources; however, there are limited data regarding factors impacting resource utilization. The purpose of this study was to evaluate variation between centers in total hospital costs for four congenital heart operations of varying complexity, and associated factors. Methods and Results The Premier Database was used to evaluate total cost in children undergoing isolated atrial septal defect (ASD) repair, ventricular septal defect (VSD) rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
83
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 96 publications
(87 citation statements)
references
References 18 publications
3
83
0
1
Order By: Relevance
“…Previous studies have suggested that LOS and postoperative complications are important drivers of high cost on a patient level; however, the impact of these variables on resource use on a hospital level has not been previously examined. 3,7 Together these variables accounted for more than a quarter of the total observed variation in our study. The impact of complications was less clear for the lower complexity operations, which may be related in part to the lower prevalence of complications in general in these patients.…”
Section: Discussionmentioning
confidence: 74%
See 4 more Smart Citations
“…Previous studies have suggested that LOS and postoperative complications are important drivers of high cost on a patient level; however, the impact of these variables on resource use on a hospital level has not been previously examined. 3,7 Together these variables accounted for more than a quarter of the total observed variation in our study. The impact of complications was less clear for the lower complexity operations, which may be related in part to the lower prevalence of complications in general in these patients.…”
Section: Discussionmentioning
confidence: 74%
“…We were also able to assess complications specific to congenital heart surgery. [3][4][5][6][7] Standardized information collected across hospitals within the PHIS Database allowed calculation of total hospital costs, which better estimate the resources consumed to carry out the service provided, compared with charge data reported in previous studies, which only reflect what the hospital billed for a service, may vary across hospitals, and overestimate cost. 6,7 These types of data linkages can maximize the strengths and mitigate the weaknesses of each data set, and allow for analyses not possible within each individual data set alone.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations